KORELASI KESETIMBANGAN FASA SISTEM CO2-C2H5OH PADA KONDISI SUBKRITIK - Sitompul, J P; Widiasa, I N; Samyudia, Y (Mesin, 1998)
This paper concerns with the correlation of phase equilibrium of binary system of carbon dioxide-ethanol at subcritical and supercritical condition. In this study, three equations of state(Redlich-Kwong, Soave-Redlich-Kwong, and Peng-Robinson) together with conventional mixing rule, were applied for correlating phase equilibrium the system. The capabilities of these equations of state were examined with experiment results obtained from the literatures. The results show that Soave-Redlich-Kwong and Peng-Robinsoh equations of states can well correlate the phase equilibrium of binary system of carbon dioxide-ethanol.